PCR: una nueva herramienta para el estudio de hongos ectomicorrícicos - Llorens, V.; Martín Esteban, María Paz; Hidalgo Hernando, Elena (Revista Catalana de Micologia, 2007)
PCR: a new tool for the study of ectomycorrhizal fungi. PCR (Polymerase Chain Reaction) is a simple technique that allows the specific amplification of particular regions of the genome of living organisms to facilitate their study. In the last few years, this and other complementary techniques have opened the field of the molecular mycology, whose Applications in detection, identification and c1assification of fungi are increasing every day. In this article, the first of a series dealing with the Molecular Techniques that can be used in Mycology, we explain the basic principies of both the PCR and two other complementary techniques commonly used for the molecular analysis of the amplified regions: RFLPs (Restriction Fragment Length Polymorphisms) and sequencing (determination ofthe primary structure ofthe nucleic acids).